Development of an open-sourced automated ultrasonic-assisted soldering system. (November 2019) - Shaffer, J.; Maassen, K.; Wilson, C.; Tilton, P.; Thompson, L.; Choi, H.; Bostwick, J.
Highlights: A modular ultrasonic-assisted soldering (UAS) platform is designed to provide precise control over process parameters. Translational and rotational motion control of the solder tip allows for leading-edge soldering. A solder wire extruder is implemented to precisely control the volume of solder deposited on the substrate. A low-cost profilometer is integrated into the system to quantify the solder wetting behavior. Preliminary experiments which characterize the solder bead geometry demonstrate a high-degree of process repeatability. Abstract: As the electronics, automobile and other industries seek to eliminate the use of flux when joining dissimilar materials, ultrasonic-assisted soldering (UAS) has emerged as a prime candidate to replace conventional soldering to improve wetting at bonded joint surfaces. A challenge for UAS is to effectively scale up techniques for industrial use. This paper presents a modular, open-sourced automated system that was designed to allow for flexible and repeatable experimentation of the UAS process. Key process parameters include solder tip speed, tip distance from the substrate, ultrasonic power supplied to the molten solder, and the extrusion rate of the solder onto the substrate. Each of these parameters are user-controlled in our automated system, which is capable of soldering a general curved path while maintaining leading-edge orientation of the soldering tip. A compatible, low-cost profilometer attachment is retrofitted to our system in order to non-destructively characterize the wetting behavior of the solder-substrate system.